3D concurrent multiscale model for crack propagation in concrete - Rodrigues, Eduardo A. [UNESP]; Manzoli, Osvaldo L. [UNESP]; Bitencourt, Luís A.G. (Elsevier, 2020)
A new approach for concurrent multiscale modeling of three-dimensional crack propagation in concrete is proposed. A macroscopic model with homogenized elastic parameters is adopted in the regions where the material behaves elastically. For regions where cracks are expected to occur, a mesoscopic model based on a mesh fragmentation technique is used to represent the concrete as a heterogeneous three-phase material composed of mortar matrix, coarse aggregates and interfacial transition zone. In this technique, standard finite elements with high aspect ratio are inserted in between all regular finite elements of the mortar matrix and in between the mortar matrix and aggregate elements in order to describe the crack initiation and propagation process by using an appropriate tensile damage constitutive model. Coarse aggregates with regular shapes are generated from a grading curve and placed into the mortar matrix randomly, using the “take-and-place” method. Coupling finite elements are used for connecting the non-matching meshes corresponding to the macro and mesoscale regions, without increasing the total number of degrees of freedom of the problem. Realistic predictions of crack formation and propagation were obtained for different tests, replicating accurately the observed experimental patterns.
Keywords: 3D multiscale analysis; Concrete crack propagation; Concurrent model; Coupling finite element; Mesh fragmentation technique; Solid finite element